2006
DOI: 10.1385/abab:134:3:249
|View full text |Cite
|
Sign up to set email alerts
|

Culture pH Affects Exopolysaccharide Production in Submerged Mycelial Culture of Ganoderma lucidum

Abstract: In submerged culture of Ganoderma lucidum, the pH optimum for cell growth has been shown to be lower than that for exopolysaccharides (EPS) formation. Therefore, in the present study, a two-stage pH-control strategy was employed to maximize the productions of mycelial biomass and EPS. When compared, a batch culture without pH control had a maximum concentration of EPS and endopolysaccharides, which was much lower than those with pH control. Maximum mycelial growth (12.5 g/L) and EPS production (4.7 g/L) were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 39 publications
1
22
0
1
Order By: Relevance
“…Baabitskaia et al [28] maintain that polysaccharide production by G. lucidum depends on such conditions as the initial pH of the substrate, C:N ratio and incubation temperature. The influence of substrate pH on polysaccharide production by G. lucidum was also reported by Kim et al [29] and Lee et al [30]. According to Prosiński [31], wood of various tree species differs with regard to the content of cellulose, lignin, hemicellulose, sugars, protein as well as other substances and shows differences in pH.…”
Section: Resultsmentioning
confidence: 62%
“…Baabitskaia et al [28] maintain that polysaccharide production by G. lucidum depends on such conditions as the initial pH of the substrate, C:N ratio and incubation temperature. The influence of substrate pH on polysaccharide production by G. lucidum was also reported by Kim et al [29] and Lee et al [30]. According to Prosiński [31], wood of various tree species differs with regard to the content of cellulose, lignin, hemicellulose, sugars, protein as well as other substances and shows differences in pH.…”
Section: Resultsmentioning
confidence: 62%
“…The pH value is always considered one of the critical indicators for mycelia growth and polysaccharide production of G. lucidum [14,15]. From the medium with or without corn oil additions, the pH profiles in cultures were observed and are shown in Fig.…”
Section: Ph Profilesmentioning
confidence: 99%
“…To accelerate BIO and EPS productions, many studies have been conducted to examine the influence of operation conditions on G. lucidum culture, including medium composition [7][8][9][10][11][12], inoculation density [13], pH [14,15], temperature [7,16], oxygen supply [17], and even cultivation process variation [18]. Furthermore, some reports have emphasized the stimulating effects on BIO and EPS productions by the addition of plant oils.…”
Section: Introductionmentioning
confidence: 99%
“…The morphological characteristics of fungal mycelia usually have a close relationship to the Xow properties of culture broth, the mycelial growth, and product formation. A few recent studies have demonstrated the close association between EPS productivity and mycelial morphology and the inXuence by various culture factors such as nutrients, and medium pH [6,12]. Fungal mycelia in a submerged culture present two major morphological forms-Wlamentous, freely dispersed Wlaments and pellets of aggregated mycelia-and the speciWc growth form in a fungal culture depends on numerous physiochemical factors [13].…”
Section: Introductionmentioning
confidence: 99%